Strategic Interactions and Portfolio Choice in Money Management : Theory and Evidence - Pedraza, Alvaro (Wiley, 2017)
I study portfolio choice of strategic fund managers in the presence of a peer-based underperformance penalty. While the penalty generates herding behavior, correlated trading among managers is exacerbated when a strategic setting is considered. The equilibrium portfolios are driven by the least restricted manager, who may vary according to the realization of returns. I compare model predictions to evidence from the Colombian pension fund management industry, where six asset managers are in charge of portfolio allocation for the mandatory contributions of the working population. These managers are subject to a peer-based underperformance penalty, which is known as the minimum return guarantee (MRG). I study trading behavior by managers before and after a change in the strictness of the MRG in June 2007. The evidence suggests that a tighter MRG results in more trading in the direction of peers, a behavior that is more pronounced for underperforming managers. I show that these findings are consistent with the qualitative and quantitative predictions of the theoretical model. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions. http://olabout.wiley.com/WileyCDA/Section/id-820227.html